Faktor-faktor yang Berhubungan dengan Partisipasi Petani Karet dalam Kegiatan Koperasi Unit Desa (KUO) Rawa Subur di Desa Mantimin Kecamatan Batumandi Kabupaten Balangan - Suherli Suherli; Suprijanto Suprijanto; Nina Budiwati (AGRIDES: Jurnal Agribisnis Perdesaan, 2015)
Cooperative is a form of social profit organization that is aimed to improve the welfare of its members through various forms of business. Participating farmers are farmers who own land and registered as a member of KUO. This cooperative providescredit to the members in order to finance member's productive businesses. The study determines the level of member participation, and identifiesthe factors related to farmer participation on KUO activities in Oesa Mantimin. The studyfinds that the level of farmer participation can be classified in the category of medium. In addition, there is a significant correlation between age and participation, but no significant correlation on education level and land acreage